The CDK4/CDK6 inhibitor PD0332991 paradoxically stabilizes activated cyclin D3-CDK4/6 complexes - Paternot, Sabine (Cell Cycle, 2014)
CDK4 and CDK6 bound to D-type cyclins are master integrators of G1 phase cell cycle regulations by initiating the inactivating phosphorylation of the central oncosuppressor pRb. Because of their frequent deregulation in cancer, cyclin D-CDK4/6 complexes are emerging as especially promising therapeutic targets. The specific CDK4/6 inhibitor PD0332991 is currently tested in a growing number of phase II/III clinical trials against a variety of pRb-proficient chemotherapy-resistant cancers. We have previously shown that PD0332991 inhibits not only CDK4/6 activity but also the activation by phosphorylation of the bulk of cyclin D-CDK4 complexes stabilized by p21 binding. Here we show that PD0332991 has either a positive or a negative impact on the activation of cyclin D-CDK4/6 complexes, depending on their binding to p21. Indeed, whereas PD0332991 inhibits the phosphorylation and activity of p21-bound CDK4/6, it specifically stabilized activated cyclin D3-CDK4/6 complexes devoid of p21 and p27. After elimination of PD0332991, these activated cyclin D3-CDK4/6 complexes persisted for at least 24 h, resulting in paradoxical cell cycle entry in the absence of a mitogenic stimulation. This unsuspected positive effect of PD0332991 on cyclin D3-CDK4/6 activation should be carefully assessed in the clinical evaluation of PD0332991, which until now only involves discontinuous administration protocols.